Engineering end-to-end IP resilience using resilience-differentiated QoS. - Autenrieth, A. (IEEE Communications magazine)
Network resilience is becoming a key issue in the design of IP-based multimedia and multiservice networks. The current discussion about IP network resilience centers around MPLS-based recovery mechanisms. Any well designed recovery strategy has to take into account the different resilience requirements of the single traffic flows in order to avoid excessive usage of bandwidth for standby links. Faced with multiple recovery options, an ISP or NSP must decide which flows to protect to what extent against network failures. In this article an extension to existing quality of service (QoS) architectures is presented that integrates the signaling of resilience requirements with the traditional QoS signaling. We refer to this extended QoS model as resilience-differentiated QoS (RD-QoS). At the border of MPLS domains, the resilience requirements can then be directly mapped to the appropriate MPLS recovery options. A traffic engineering process for the provisioning of the resilience classes is introduced, and a case study demonstrates the significant network capacity savings achievable via this approach